2020
DOI: 10.1155/2020/6678158
|View full text |Cite
|
Sign up to set email alerts
|

Multimode Traffic Travel Behavior Characteristics Analysis and Congestion Governance Research

Abstract: The rapid aggregation of modern urban population and the rapid growth of car travel lead to traffic congestion, environmental pollution, and other problems. In view of the limited land resources in our country, it is impractical to meet residents’ travel demand by blindly increasing traffic supply. Therefore, addressing the urban road congestion problem for sustainable development of modern cities, the paper makes research on residents’ travel behavior characteristics and travel preference under the condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Rapid urban population growth brings with it severe ground traffic congestion, which increases citizens' commuting time and causes environmental pollution [1][2][3]. The development of the metro system can effectively alleviate this issue in many countries, especially in China [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid urban population growth brings with it severe ground traffic congestion, which increases citizens' commuting time and causes environmental pollution [1][2][3]. The development of the metro system can effectively alleviate this issue in many countries, especially in China [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, numerical simulation is used to analyze the in uence of the changes of di erent parameters on travel guidance under the VMS information release strategy. Assume that the road network structure in a large-scale activity area for the calculation is a Nguyen-Dupuis network [25], as shown in Figure 6. e network has two starting points (entrances to the large-scale activity area) and two destinations (places for activity).…”
Section: Scenario and Parametersmentioning
confidence: 99%
“…However, the sensitivity of mode choice behaviour is also often influenced by travel characteristics [32]. In a study conducted in Valencia, Spain, Arroyo et al [33] found that travel with single characteristics (solo) tends to be easier to adapt to sustainable transport programmes.…”
Section: Hypothesis Developmentmentioning
confidence: 99%